CONVENIENT OF MEDICINE TRADITIONAL TOPOKE IN THE CHEFFERIE OF THE BOLOMBOKI (RD CONGO). - ASAKA John, ANGONDO; ELANGA ATILAMBISA, Felix; YENGA KUMIEPALI, Alain; MAPANZA MOLIYA, Aimé; BOYEMBA AYOMBA, Salthiel; MUTEBA LUKALAMBA, Claude; WINGENGA-WI-EPENDO, Jeannot (IJRDO - Journal of Social Science and Humanities Research, 2019)
This survey centered on the practices of medicine traditional "Topoké" in the Chefferie of the Bolombokis exposes the autonomous traditional practices clean to the" Topokés ". This medicine takes care of the natural and supernatural or mystical illnesses. It is not for us in this work about denying the interest of the conventional medicine that could prove his/her/its efficiency in many cases but to show the manner of which the inhabitants of the chefferie of the Bolombokis elaborate their own notion of illness through their own practices, their own experiences because the cultural diversity is complex and is a cultural reality.   The objectives assigned in this survey, are the next one: to identify the main reasons of the recourse of the majority of populations of the chefferie of Bolomboki to the traditional medicine; to Identify the representations socio-cultural of the populations of the Bolomboki chefferie on the Congolese traditional medicine; to Identify and to demonstrate the elements that contribute to the construction of this socio-cultural representation; to Identify the nature, the type of the social reports that exists between the tradi-practitioners and the patients.